Transposición de suelos como técnica de restauración de vegetación degradada en un ecosistema andino de la hoya de Loja - González Nivelo, Leonardo Paúl (2024)
Forests have been reduced as a result of anthropogenic activities, which has caused the loss of vegetation and land degradation. This research aims to evaluate the contribution to specific diversity using the soil transposition technique as an alternative to restore areas degraded by agricultural activities. Three reference areas were selected: forest, shrub thicket and succession, in which 5 soil samples were obtained, with dimensions of 30 * 30 cm and 5 cm deep, subsequently they were translocated in the degraded area by the agriculture in some random blocks. The seed bank was monitoring during seven months in the transpositions, where the diversity contribution was evaluated through floristic composition, structural parameters, survival, diversity indices, vegetation dynamics (germination, coverage) and similarity. Additionally, the biological and edaphic conditions were characterized such as: texture, apparent density, porosity, pH, organic matter and carbon in the reference area. The forest and succession provided greater diversity with herbaceous and shrubby species, mainly from the families Asteraceae, Solanaceae and Cyperaceae, and the only arboreal type Siparunaceae. The succession and forest reported: high survival (> 80%) otherwise, the shrub thicket with medium survival (~50%) and the cover was dominated by Acalypha Stenoloba, Erigeron Canadensis, Phytolacca Bogotensis, Oxalis corniculata. Furthermore, the forest and succession reported high similarity in their floristic composition. Finally, it was determined that soil transposition is essential for restoration, because it accelerates successional processes which allows the establishment of future communities with native species and ecological interest.